Medicolegal Aspects of Nursing Practice in the Emergency Room of Bhayangkara Hospital, Semarang - Syela Ambri Yudhana; Andri Winjaya Laksana (UNISSULA Semarang, 2025)
Abstract. This study aims to analyze the implementation of medicolegal legal aspects in nursing practice at the Emergency Department (ED) of Bhayangkara Hospital Semarang, identify the constraints faced, and formulate efforts to improve understanding and implementation. This research uses empirical legal research methods with a sociological juridical approach and a case study design. Data were obtained through in-depth interviews with the Head of the ED, observation, and documentation studies, which were then analyzed using qualitative data analysis techniques from the Miles and Huberman model. The results show that the implementation of medicolegal aspects in the ED of Bhayangkara Hospital Semarang has generally been carried out in accordance with applicable professional standards and regulations, with nurses having carried out legal responsibilities (civil, criminal, administrative) as well as independent and collaborative authority based on Law No. 38 of 2014 concerning Nursing. However, several main constraints were found, namely: (1) the lack of patient family understanding of legal provisions in emergency situations; (2) misconceptions regarding the limits of nurses' authority; (3) documentation constraints in emergency conditions; (4) communication barriers with patient families; and (5) limited resources and regulatory complexity. Based on these findings, this study recommends a series of comprehensive improvement efforts, including continuous education for nurses, development of efficient documentation systems, improved communication with patient families, strengthening institutional support, and public education.